Influence of the temperature on the formation of a phenolic resol resin catalyzed with amine - Astarloa Aierbe, G. (2002)
The influence of the condensation temperature on the phenolic resol resin prepolymer formation was studied by liquid chromatography and carbon nuclear magnetic resonance (13C NMR) spectroscopy. Four resols catalyzed with triethylamine and with initial pH = 8.0 and F/P = 1.8 were synthesized at 60, 80, 95°C, and reflux (98-102°C). On increasing the condensation temperature, reactant consumption rates and first formed addition products increased, condensation times decreased as well. Prepolymer synthesized at refluxing temperatures showed higher formaldehyde addition onto ortho positions with respect to the other resols. Different types of phenolic rings connecting bonds were observed: para, para and ortho, para bridges as well as ether bonds were detected. No ortho, ortho bonds were observed for the condensation with the catalyst used. 13C NMR measurements did not show qualitative differences between prepolymers. Anyway, residual phenol and formaldehyde concentrations and the amount of free unreacted ortho and para positions decreased with temperature.